ANALISIS PENGARUH KEPUASAN KERJA TERHADAP TURNOVER INTENTIONS PEGAWAI KOPERASI SIMPAN PINJAM MUGI LESTARI - ., Suroso (Jurnal Manajemen dan Bisnis Kreatif, 2015)
ABSTRACT This research aims at analyzing the influence employee job satisfaction toward turnover intentions employees. The proposed hypotheses: The job satisfaction have significance influence to the employee’s turnover intentions. The result of the research has evidenced that the employee’s job satisfaction significantly influence to turnover intentions employees. And the conclution is that the job satisfaction have significance negative influence to the employee’s turnover intentions Keyword: Job satisfaction, Turnover intentions